Family planning : a global handbook for providers - evidence-based guidance developed through worldwide collaboration (WHO, and Center for Communication Programs (CCP), Baltimore GenevaCH, 2011)
Offers technical information to help health care providers deliver family planning methods appropriately and effectively. Provides specific guidance on 20 family planning methods and addresses many of the providers' different needs, from correcting misunderstandings to managing side effects. Covers related health issues that arise in the context of family planning
Keywords: FAMILY PLANNING